Unmet Needs in Patients With Heart Failure: The Importance of Palliative Care in a Heart Failure Clinic - Gonzalez-Jaramillo, Valentina; Maessen, Maud; Luethi, Nora; Guyer, Jelena; Hunziker, Lukas; Eychmüller, Steffen; Zambrano, Sofia C. (Frontiers in Cardiovascular Medicine, 2022)
Background There are increasing calls to establish heart failure (HF) clinics due to their effectiveness in the interdisciplinary management of people living with HF. However, although a recommendation exists for palliative care (PC) providers to be part of the interdisciplinary team, few of the established HF clinics include them in their teams. Therefore, in this qualitative study, we aimed to understand the unmet PC needs of patients with HF attending an already established HF clinic. Methods Secondary qualitative analysis of structured interviews undertaken within a larger study to validate the German version of the Needs Assessment Tool: Progressive Disease—Heart Failure (NAT: PD-HF). The NAT: PD-HF is a tool that aims to assess unmet needs in patients with HF. The interviews took place between January and March 2020 with patients from the ambulatory HF Clinic of a University Hospital in Switzerland. For this analysis, we transcribed and thematically analyzed the longest and most content-rich interviews until we reached data saturation at 31 participants. The interviews lasted 31 min on average (24–48 min). Results Participants (n = 31) had a median age of 64 years (IQR 56–77), the majority had reduced ejection fraction, were men, and were classified as having a New York Heart Association functional class II. Participants were in general satisfied with the treatment and information received at the HF clinic. However, they reported several unmet needs. We therefore identified three ambivalences as main themes: (I) “feeling well-informed but missing essential discussions”, (II) “although feeling mostly satisfied with the care, remaining with unmet care needs”, and (III) “fearing a referral to palliative care but acknowledging its importance”. Conclusion Although patients who are receiving multidisciplinary management in ambulatory HF clinics are generally satisfied with the care received, they remain with unmet needs. These unmet needs, such as the need for advance care planning or the need for timely and tactful end-of-life discussions, can be fulfilled by PC providers. Including personnel trained in PC as part of the multidisciplinary team could help to address patients' needs, thus improving the quality of care and the quality of life of people living with HF.